KEWENANGAN PENGADILAN NIAGA MEMERIKSA PERKARA KEPAILITAN YANG MEMUAT KLAUSUL ARBITRASE DALAM PERJANJIAN (Studi Kasus Putusan Nomor 64/Pailit/2012/PN.Niaga.Jkt.Pst) - D. Adam Fairuz; Marjo Marjo; Zil Aidi (Diponegoro Law Journal, 2022)
The objection of this research is intended to determine how far the authority of Commercial Court in settling bankruptcy case that contain arbitration clause in its agreement and analyze the decision Number 64/Pailit/2012/PN.Niaga.Jkt.Pst regarding its compliance with the laws and regulations, theories, and expert opinions. This research uses a normative juridical method with descriptive analytical research specifications to explain the authority of the Commercial Court in settling disputes that contain an arbitration clause in its agreement. The results of the study indicate that there are differences of opinion from scholars regarding Arbitration (extra judicial power) and its absolute authority over the arbitration clause, as well as the absolute authority of the Commercial Court (extraordinary power) in bankruptcy cases. The enactment of Law Number 37 of 2004 confirms in Article 303 that when there is an arbitration clause in a dispute filed through bankruptcy, the Commercial Court has absolute authority.